TARI KREASI BARU LABAONG LABUNTAR - KOMPYANG AYU, NI GUSTI AYU MADE AMBAR; Sutapa, I Ketut; Suminto, Suminto (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2024)
Labaong Labuntar is a new creation of dance art originating from the folklore of Sumbawa, West Nusa Tenggara, depicting the character of two princess characters named Lala Balong and Lala Buntar from the Samawa Kingdom. The idea for this work is motivated by a social phenomenon, namely friendship relationships. The process or stages of creation that are followed include: (1) Ngawirasa (inspiration), (2) Ngawacak (exploration), (3) Ngeplan (conception), (4) Ngawangun (execution), (5) Ngebah (production). This work is realized in the form of a new dance creation consisting of two female dancers depicting their respective characters, namely Lala Balong and Lala Buntar. The structure of this work is divided into three parts, namely beginning, content and end. The dance accompaniment used in this work is Gong Genang with the addition of several instruments such as satong srek, gendang, pelompong, and serune. The